Investigação do ruído gerado por instalações hidrossanitárias em uma edificação multifamiliar - Pavanello, Lívia Ribeiro (2014)
In Brazil, the noise generated by plumbing systems into buildings is still little studied. Despite residents of multi-family vertical building citing this pathology as a cause of discomfort and complaints, there is not yet a standard that regulate noise measurements of hydrosanitary installations in the country in loco. This paper has as objective to establish an adequate measurement procedure of sound pressure level based in ISO 16032 (ISO, 2004) appropriate to evaluation the noise of plumbing systems, executed according to national standards, aiming to provide acoustic comfort to users. To verify the standard applicability, a 10 floor residential building, not inhabited yet, in the city of Santa Maria, with reinforced concrete structure and masonry wall, was chosen. The hydrosanitary devices measured were the faucet of the sink and the flushing cistern of the toilet bowl, both located in the master bathroom of the background apartments. The measurements was realized in suites, in 5 floors, and in the master bathroom of the 9th floor. The general rule was that the sanitary devices to be measured were triggered in the master bathroom, of the autonomous unit situated 1 floor above the suite, where was the microphone. However, exceptions occurred on the 10th and on the 7th floor, where measurements were made relating to hydrosanitary devices of the same floor and of two floors above, respectively. Therefore were measured and subsequently analyzed, all quantities allowed by ISO 16032 (ISO, 2004), in the weighting A and C, they are: Leq,nT, LFmax,nT and LSmax,nT. Were also performed measurements of the reverberation time of the suites according to ISO 3382-2 (ISO, 2008). After analyzing the results, it was found that in the situation of measurements, some results of the sink were influenced or masked by residual noise. Finally, to ensure the usefulness of the measurement procedure used, the results were compared with unique values expressed in NBR 15575-6 (ABNT, 2013) and was then evaluated the performance of hydrosanitary installations of the building, in situations that apply to standard. It is considered, therefore, that this paper contributed to the improvement of studies that search to enlarge the acoustic comfort in the Brazilian buildings, to establish measurement procedure of sound pressure level for the noise evaluation of plumbing systems.